Standar Pelayanan Publik di Masa Pandemi Covid-19: Studi Pelayanan Perpustakaan ITERA - Febri Ramadhan, Rydho; Tamaya, Vicka (Jurnal Studi Ilmu Sosial dan Politik, 2021)
Purpose: This paper examined changes in public services during the pandemic. Research Methodology: The approach taken in this study was qualitative. Researchers collected information and data through the interview method. Along with conducting interviews, researchers searched for and read various pieces of information about implementing ITERA library services via the website and Standard Operating Procedures for services during the pandemic. Results: The Covid-19 pandemic affects public services, most notably at the ITERA Library. Changes to the ITERA Library Public Service Standards resulted in innovations in the Sumatra Institute of Technology Library's services.